Explorations in twentieth-century theology and philosophy people preoccupied with God - Loades, Ann 1938-2022 (Anthem Press, 2023)
Ann Loades has been instrumental in bringing forward for the attention of readers in later generations 'voices from the past,' notably highlighting the work of pioneering women such as Evelyn Underhill and Dorothy L. Sayers as well as advancing the study of better-known Anglican forebears C. S. Lewis and Austin Farrer-always with her own distinctive concerns. A key interpreter of the Anglican tradition and with a keen eye to ensure the full recognition of women, these studies by Ann Loades are essential reading in Anglican, feminist, and twentieth-century theology